Urine trace element disorder along with renal function injury in vitamin D deficient diabetic rats and intervention effect of 1α,25-dihydroxyvitamin D3 - Wang, Dongxia; Wang, Ning; Zhou, Juan; Luo, Gang; Li, Yanyan; Yu, Wei; Tan, Hongxing; Liu, Gang; Wang, Jun; Hao, Liping (Frontiers in Nutrition, 2022)
Trace element metabolism disorders are often secondary to disorders of glucose metabolism in diabetes. Although 1α,25-dihydroxyvitamin D3 (1,25(OH)2D3) could ameliorate abnormal glucose metabolism in the development of diabetes, the effect on trace element metabolism is unclear. The objective of this study was to evaluate the influence of 1,25(OH)2D3 on urinary excretions of trace elements in Zucker diabetic fatty (ZDF) rats. At 6 weeks of age, male ZDF (n=40) rats were subdivided into four groups: diabetic model (ZDF), low-dose (ZDF+VL, 2 μg/kg·bw), middle-dose (ZDF+VM, 8 μg/kg·bw) and high-dose (ZDF+VH, 16 μg/kg·bw) 1,25(OH)2D3 groups. Another 10 Zucker lean (ZL) rats served as a control group. All rats were given vitamin D deficient Purina #5008 chow and the intervention groups were given the corresponding dose of 1,25(OH)2D3 by gavage on alternate days for 7 weeks. Microalbuminuria (MALB) and urinary creatinine concentration were detected by a biochemical autoanalyzer. Urine trace element concentrations were measured using inductively coupled plasma mass spectrometry (ICP-MS) and were corrected by urinary creatinine. Throughout the intervention phase, MALB, UACR and urinary creatinine levels in the ZDF group were significantly higher than those in the ZL group, and showed a gradual increase with the prolongation of the intervention time. These changes were reversed in a dose-dependent manner after 1,25(OH)2D3 intervention (P < 0.05). Correspondingly, most of the urinary trace element excretions in the ZDF rats were significantly increased compared with the ZL group, and 1,25(OH)2D3 intervention significantly reduced the urinary copper (Cu), zinc (Zn), selenium (Se) and molybdenum (Mo) levels in the ZDF rats (P < 0.05), especially in the medium and high dose groups. 1,25(OH)2D3 had improvement effects on urinary Cu, Zn, Se, and Mo excretions in ZDF rats, suggesting that it may be related to the reduction of diabetic renal impairment and renal oxidative damage.